Correlation of hypothyroidism and dyslipidemias with plantar fasciitis in Indian population - Tandel, Jignesh Y.; Wagh, Aniket A.; Jagtap, Kapil R.; Kantharia, Sanjay; Bharadwaj, Bharath; Jain, Akash; Puri, Shivakant; Kakde, Shirish (International Journal of Research in Orthopaedics, 2023)
Background: Plantar fasciitis (PF) affects millions of people but still there is lack of knowledge of all the factors involved in causing this condition. The main objective of this study is to investigate the relationship between thyroid hormones, dyslipidemias, hyperuricemia, liver and renal function tests. Methods: 200 patients were enrolled,100 with a clinical diagnosis of PF in the case group and 100 without PF in the control group. Patients thyroid profile (T3, T4, TSH), liver profile (Bilirubin, SGOT, SGPT), renal profile (Serum creatine, urea), lipid profile (serum total cholesterol, LDL, HDL, VLDL, triglyceride) and uric acid levels were checked and compared between the two groups. Results: Patients with PF had a higher TSH level with a mean of 4.33 mg/dl (range 0.64-20.56) than the control group with TSH mean of 2.51 mg/dl (range 0.51-8.78) (p<0.001). Serum cholesterol level was significantly higher in patients with PF than in the control group (p=0.002). Triglycerides (p=0.01), LDL (p<0.01), VLDL (p=0.021) were significantly higher in patients than in controls. HDL levels were found to be significantly lower in patients than in controls (p=0.003). Conclusions: Significantly higher TSH levels, serum cholesterol, serum triglyceride, serum LDL, serum VLDL and low HDL levels were seen in the Indian population suffering from PF. Thus, hypothyroidism and dyslipidemias should be evaluated while treating PF.